Types of Code Switching Used by Parents on Instagram - Ni Putu Novia Lestari; I Dewa Ayu Devi Maharani Santika; Ni Nyoman Deni Ariyaningsih (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2022)
Code switching is a phenomenon that will always occurs in bilingual community. People will consciously do code switching in their communication when they have the ability to speak two or more languages. It occurred not only in oral communication but also when they used written form communication on social media like Instagram. This study aimed to analyze the types and speech function of code switching found in parents’ comments on Instagram. This study used qualitative descriptive method to create clear and well organize analysis of the data. The data itself collected from Parentalk.ID Instagram comment section, from feeds posted on May until October 2021. In analyzing the data, the writer used the theory proposed by Romaine (1995) to identify the types of code switching and Appel & Muysken (1987) to analyze the speech functions of code switching from the data source. The study concluded that the most types of code switching used is intra-sentential switching and the speech functions are metalinguistic function that used to show off someone’s language skill and referential function that occurred because of lack of knowledge or language facility